Impact of Communication on Human Health - Qasim Sharif, Raghad Latif; Abs Abd, Firas Hamzah; Farhood Mohi, Shahad Hussein; Ali Mohammed, Siham Aqeel (American Journal of Biomedicine and Pharmacy, 2024)
Electromagnetic waves are a form of energy generated by the oscillation of electrical charges that make up the atom. These waves consist of electric and magnetic components and travel at the speed of light (3 × 10^8 m/s). Radio waves, which are the lowest in the electromagnetic spectrum, are primarily used for communication. They are a type of electromagnetic wave with the longest wavelengths in the spectrum and the lowest frequencies, ranging between 30 Hz and 300 GHz. Mobile communication towers are structures comprising transmitters and receivers for radio waves. These towers are interconnected and consist of steel columns forming a cohesive network, mounted on independent ground bases. They carry antennas that send and receive wireless frequencies. These towers are classified into two types: main towers and secondary towers. Telecommunications companies continually work to increase the number of mobile signal boosters to provide high-quality service to their subscribers. Without these stations or with insufficient numbers, service quality would be inadequate. The harmful effects of electromagnetic radiation emitted by mobile phone antennas are often imperceptible and invisible. Telecommunications companies are required to adhere to environmental regulations when establishing the infrastructure for mobile networks. These include standards and conditions set by the Environmental Affairs Authority, which must be followed both during construction and operation.